Pengaruh Kedalaman Sarang Penetasan Penyu Hijau (Chelonia mydas) terhadap Masa Inkubasi dan Persentase Keberhasilan Penetasan di Pantai Sukamade, Taman Nasional Meru Betiri, Banyuwangi Jawa Timur [Effect of Nesting Site Depth of Green Turtle (Chelonia mydas) on the Incubation Period and Hatching Success Percentage in Sukamade Beach, Meru Betiri National Park, Banyuwangi in East Java] - Laksmi Sulmartiwi; Wahju Tjahjaningsih; Abang Aldhian R. Putera (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Indonesia is an archipelago that is rich in diversity of flora and fauna. One of these is a wealth of fauna species of sea turtles. All species of sea turtles in the world by the Convention on International Trade in Endangered Species of Wild Flora and Fauna (CITES) put in Appendix I as endangered and protected and not allowed to be traded. The purpose of this study was to determine effect the ratio of the depth from nest egg incubation and hatching percentage of green turtles (Chelonia mydas) nests at different depths in Sukamade, Betiri Meru National Park, Banyuwangi, East Java. The design of the study is a randomized block design (RGD). The groups as replicates for RGD, between groups or experimental material media are considered uniform. The results showed that the average incubation period was 58.87 +0.39 days, then the results were followed by Duncan's multiple range test, which showed that the highest yield obtained by the depth of 50 cm wasn't significantly different (p> 0.05) with depth of 30 cm and 70 cm. While the results obtained at the lowest depth of 90 cm was significantly different (p <0.05) with the other depth (30 cm, 50 cm and 70 cm). While the percentage of hatching success obtained in average hatching was 88.12 + 0.38%. The Duncan's multiple range test analysis, showed that at a depth of 70 cm were not significantly different (p <0.05) from depth of 50 cm, but 70 and 50 cm depth was significantly different (p> 0.05) from another depth. Whereas the lowest hatching results obtained on depth of 90 cm are significantly different (p> 0.05) from the other depth (30 cm, 50 cm and 70 cm). The conclusion of this study was different depth of green turtle nests affect the egg incubation period and the percentage of egg hatching success of green turtles.